How do countries specialize in food production? A complex-network analysis of the global agricultural product space - Mercedes Campi; Marco Duenas; Giorgio Fagiolo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
In the last years, there has been a growing interest in studying the global food system as a complex evolving network. Much of the literature has been focusing on the way countries are interconnected in the food system through international-trade linkages, and what consequences this may have in terms of food security and sustainability. Little attention has been instead devoted to understanding how countries, given their capabilities, specialize in agricultural production and to the determinants of country specialization patterns. In this paper, we start addressing this issue using FAO production data for the period 1993-2013. We characterize the food production space as a time-sequence of bipartite networks, connecting countries to the agricultural products they produce, and we identify properties and determinants underlying their evolution. We find that the agricultural product space is a very dense network, which however displays well-defined and stable communities of countries and products, despite the unprecedented pressure that food systems have been undergoing in recent years. We also find that the observed community structures are not only shaped by agro-ecological conditions but also by economic, socio-political, and technological factors. Finally, we discuss the implications that such findings may have on our understanding of the complex relationships involving country production capabilities, their specialization patterns, food security, and the nutrition content of the domestic part of their food supply.
Keywords: Q18; E23; N50; 330; Food systems; Food production; Specialization; Bipartite networks; Community structure detection; Hypergeometric filtering